2007
DOI: 10.1002/jssc.200600306
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of various extraction techniques for isolation and determination of isoflavonoids in plants

Abstract: In the present paper, the following extraction techniques have been used for extracting isoflavonoids from the species Matricaria recutita, Rosmarinus officinalis, Foeniculum vulgare, and Agrimonia eupatoria L.: supercritical fluid extraction (SFE), pressurized fluid extraction, matrix solid phase dispersion, ultrasonic extraction in an ultrasonic bath (USE) and by means of an ultrasonic homogeniser (HOM), extraction by means of Soxhlet apparatus (SOX), and solid phase extraction. Experimental optimization of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…But even without the markers, one can still use this method to quickly prepare crude extracts for bioactivity screening. Anand et al [17] compared three methods including PLE for extracting the bioactive molecules in Hypericum perforatum L. PLE was found to be more effective in extracting caffeine, phytol, palmitic, and stearic acid in mate tea leaves (Ilex paraguariensis) and in shortening the total extraction time and reducing solvent consumption [18], the same conclusions drawn by many other investigators [19][20][21][22]. PLE was also effective in extracting terpenes, fatty acids and Vitamin E [23] as well as giving a high total extract yield [24] but less effective in extracting sterols [25] and caffeine from green tea leaves [26].…”
Section: Preparation Of Botanical Samples For Initial Screening Testsmentioning
confidence: 67%
“…But even without the markers, one can still use this method to quickly prepare crude extracts for bioactivity screening. Anand et al [17] compared three methods including PLE for extracting the bioactive molecules in Hypericum perforatum L. PLE was found to be more effective in extracting caffeine, phytol, palmitic, and stearic acid in mate tea leaves (Ilex paraguariensis) and in shortening the total extraction time and reducing solvent consumption [18], the same conclusions drawn by many other investigators [19][20][21][22]. PLE was also effective in extracting terpenes, fatty acids and Vitamin E [23] as well as giving a high total extract yield [24] but less effective in extracting sterols [25] and caffeine from green tea leaves [26].…”
Section: Preparation Of Botanical Samples For Initial Screening Testsmentioning
confidence: 67%
“…First of all the suitable solvent was selected. Because of our previous experiences [20] only the mixtures ACN -water at various ratios were tested. Based on the obtained results (not presented) the 30% v/v ACN was selected as the extraction solvent and was used for further experiments.…”
Section: Ultrasonic Extraction Methods Optimisationmentioning
confidence: 99%
“…In addition to the traditional extraction methods i.e. maceration, percolation, soxhilation which have been used for decades, newer techniques like accelerated solvent extraction, extraction using ultra sonication, microwave assisted extraction (Rostagno et al 2007), supercritical fluid extraction (Cheng et al 2011;Klejdus et al 2005aKlejdus et al , 2010Rostagno et al 2002), ionic liquid based ultrasonic assisted extraction (ILUAE), solid phase extraction (SPE) and pressurized liquid extraction (PLE) (Bajer et al 2007;Rostagno et al 2004) have been increasingly reported for the isolation of isoflavonoids from plant products. These techniques were developed for application in natural product extraction owing to their advantages with regard to the extraction time, reproducibility and better yields due to elevated pressure and temperature which lead to better penetration of extraction solvent to the matrix pores.…”
Section: Extraction Of Isoflavonoidsmentioning
confidence: 99%
“…heartwood, seeds, leaves, rhizomes, roots etc. The need for sample preparation depends strongly on the sample type and the analysis techniques to be employed (Bajer et al 2007). Extraction technique, extraction solvent, pH of the solvent, extraction time, temperature, sample to solvent ratio, sample characteristics are the defining factors that affect extraction efficiency, isoflavonoids profile and recovery (Rostagno et al 2010).…”
Section: Extraction Of Isoflavonoidsmentioning
confidence: 99%